Penyusutan Kualitas Telur akibat Peningkatan Ukuran Rongga Udara, dan pH Telur Ayam Ras - Weny Dwi Ningtiyas; Andi Nurul Mukhlisah; Muhammad Irfan; Samsu Alam Rab; Andi Mutmainna (Pascasarjana Institut Agama Islam Sunan Giri Ponorogo, 2023)
Eggs are a source of animal protein because they have complete nutrition, but easily damaged and contaminated if not handled properly. The distribution of Layer chicken eggs in traditional markets does not pay attention with good packaging process, besides the time duration could last for a long time, the sellers also do not pay attention to the cleanliness of the sales place which can cause a decrease in the quality of eggs. Therefore, when consuming eggs, buyers should pay attention to their quality. This research aimed to aalyze the factors that cause of decline in egg quality. This research used 45 Layer chicken eggs obtained from the traditional market in Majene city, West Sulawesi Province. The data obtained was analyzed using descriptive analysis by looking at the average value and standard deviation. Researched shows that the quality of Layer chicken eggs in traditional market of Majene city has decreased but still in good category and safe for consumption.